Population Pharmacokinetics of Mycophenolic Acid Co-Administered with Tacrolimus in Corticosteroid-Free Adult Kidney Transplant Patients - Rong, Yan; Mayo, Patrick; Ensom, Mary H. H.; Kiang, Tony K. L. (Clinical pharmacokinetics, 2019)
Background and Objective Mycophenolic acid is commonly prescribed to adult kidney transplant recipients. Mycophenolic acid is extensively metabolized to mycophenolic acid-glucuronide (major metabolite) and mycophenolic acid-acyl-glucuronide (minor metabolite). We hypothesized that (1) adult kidney transplant patients on corticosteroid-free regimens exhibit unique mycophenolic acid population pharmacokinetics compared with patients receiving corticosteroid-based therapy, and (2) mycophenolic acid clearance is directly dependent on glucuronide metabolite formation. Methods Non-linear mixed-effects modeling was conducted with MonolixSuite-2018R1 ( n = 27). Optimal pharmacokinetic models were selected based on objective function values, standard errors, and biological plausibility. Results Clinical demographic data were sex (female, 16), age (47 ± 13 years, mean ± standard deviation), weight (70 ± 16 kg), height (165 ± 9 cm), albumin (43 ± 4 g/L), serum creatinine (102 ± 27 µmol/L), estimated glomerular filtration rate (61 ± 16 mL/min/1.73 m 2 ), mycophenolic acid dosage (1.4 ± 0.5 g/day, as mycophenolate mofetil), and tacrolimus dosage (5 ± 3 mg/day, immediate release). The population pharmacokinetics of mycophenolic acid can be described by a two-compartment first-order absorption with lag time, and a linear elimination structural model. The apparent oral clearance estimate in the final model (population mean, relative standard error) was 2.87 L/h, 42.3%, which is lower than that reported for similar patients on corticosteroid-based regimens (11.9–26.3 L/h). Other pharmacokinetic parameters were comparable to historical data obtained in corticosteroid-based patients. Both mycophenolic acid-acyl-glucuronide trough concentration and the area under the concentration–time curve ratio were significant covariates that reduced mycophenolic acid apparent oral clearance from 16.5 (base model) to 2.87 L/h. The model was evaluated based on bootstrapping, visual predictive checks, and diagnostic plots. Conclusions Our novel findings suggest the potential need to reduce mycophenolic acid dosage in subjects on corticosteroid-free regimens. Corticosteroid-free subjects may also be more sensitive to drug/gene interactions.